Effects of Protected Areas on Forest Cover Change and Local Communities: Evidence from the Peruvian Amazon - Juan José Miranda; Leonardo Corral; Allen Blackman; Gregory Asner; Eirivelthon Lima (Inter-American Development Bank (IDB), 2014)
Protected areas are a cornerstone of forest conservation in developing countries. Yet we know little about their effects on forest cover change or the socioeconomic status of local communities, and even less about the relationship between these effects. This paper assesses whether 'win-win' scenarios are possible-that is, whether protected areas can both stem forest cover change and alleviate poverty. We examine protected areas in the Peruvian Amazon using high-resolution satellite images and household-level survey data for the early 2000s. To control for protected areas nonrandom siting, we rely on quasi-experimental (matching) methods. We find that the average protected area reduces forest cover change. We do not find a robust effect on local communities. Protected areas that allow sustainable extractive activities are more effective in reducing forest cover change but less effective in delivering win-win outcomes.
hdl:11319/6755
Keywords: Q56; Q23; Q24; R14; R52; 330; conservation; deforestation; protected areas; poverty; land use; land conservation